2014
DOI: 10.1097/ta.0000000000000272
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric outcomes for trauma patients in the state of Florida after the advent of a large trauma network

Abstract: Epidemiologic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…229 The description for this network included a statement that government policy had been put in place to monitor development, but no outputs have been identified. (b) Studies reporting data on activity within clinical networks for specific conditions such as stroke, 230,231 trauma, 232,233 primary or community care 234,235 and ST elevation myocardial infarction. 236 Most of these studies claimed that clinical networks had improved care by, for example, increasing numbers of patients admitted to specialist facilities, 230,232 receiving thrombolysis for stroke 231 and improving mortality from trauma, 233 but all of them reported current activity and had not made any assessment of differences in care compared with before the network became operational or, therefore, whether the network had improved care.…”
Section: Resultsmentioning
confidence: 99%
“…229 The description for this network included a statement that government policy had been put in place to monitor development, but no outputs have been identified. (b) Studies reporting data on activity within clinical networks for specific conditions such as stroke, 230,231 trauma, 232,233 primary or community care 234,235 and ST elevation myocardial infarction. 236 Most of these studies claimed that clinical networks had improved care by, for example, increasing numbers of patients admitted to specialist facilities, 230,232 receiving thrombolysis for stroke 231 and improving mortality from trauma, 233 but all of them reported current activity and had not made any assessment of differences in care compared with before the network became operational or, therefore, whether the network had improved care.…”
Section: Resultsmentioning
confidence: 99%
“…The delayed physical response to injury in the aging population makes it difficult to distinguish the best triage and management options. In previous studies, advanced age is a reported risk factor predicting poor clinical outcomes in traumatic injuries [ 16 ]. Aggressive management and intensive monitoring are necessary in the geriatric traumatic population, including aggressive resuscitation and more image studies.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of our data suggests age is an important factor affecting transfer. It is well known that populations at extremes of age are much more likely to suffer morbidity from traumatic injuries and benefit from early transfer to designated trauma centers [ 24 29 ]. Pediatric trauma patients have been shown to have higher in-hospital mortality, length of stay, and cost of care in adult hospitals than pediatric-centered hospitals [ 25 ].…”
Section: Discussionmentioning
confidence: 99%